Pengobatan Tradisional Penyakit Herpes (Dompo) pada Masyarakat Suku Jawa di Desa Pon Kecamatan Sei Bamban Kabupaten Serdang Bedagai - Anggi Ratulangi; Nuriza Dora (LPPM Politeknik Pratama, 2024)
This research examines the beliefs of the Javanese people regarding the traditional treatment of herpes (dompo) in Pon Village by using a spraying method which can only be carried out by married couples with special requirements which is still carried out today. This type of research uses qualitative research with an ethnographic method. Data collection techniques were carried out by means of observation, interviews and documentation studies. The aim of this research is to examine the beliefs of the Javanese people regarding traditional treatment for dompo disease and procedures for its treatment. The results of this research explain the knowledge of Javanese people regarding dompo treatment that has been passed down from generation to generation. The conclusion of this research is that the Javanese people still use traditional healing methods which are still maintained to this day.